Hollow colloidosomes prepared using accelerated solvent evaporation - Shahidan N.N.; Liu R.; Thaiboonrod S.; Alexander C.; Shakesheff K.M.; Saunders B.R. (American Chemical Society, 2013)
We demonstrate a new, scalable, simple, and generally applicable two-step method to prepare hollow colloidosomes. First, a high volume fraction oil-in-water emulsion was prepared. The oil phase consisted of CH2Cl2 containing a hydrophobic structural polymer, such as polycaprolactone (PCL) or polystyrene (PS), which was fed into the water phase. The water phase contained poly(vinylalcohol), poly(N-isopropylacrylamide), or a range of cationic graft copolymer surfactants. The emulsion was rotary evaporated to rapidly remove CH2Cl2. This caused precipitation of PCL or PS particles which became kinetically trapped at the periphery of the droplets and formed the shell of the hollow colloidosomes. Interestingly, the PCL colloidosomes were birefringent. The colloidosome yield increased and the polydispersity decreased when the preparation scale was increased. One example colloidosome system consisted of hollow PCL colloidosomes stabilized by PVA. This system should have potential biomaterial applications due to the known biocompatibility of PCL and PVA